2021
DOI: 10.3390/ijms22041893
|View full text |Cite
|
Sign up to set email alerts
|

Novel Genetically Modified Mouse Model to Assess Soman-Induced Toxicity and Medical Countermeasure Efficacy: Human Acetylcholinesterase Knock-in Serum Carboxylesterase Knockout Mice

Abstract: The identification of improved medical countermeasures against exposure to chemical warfare nerve agents (CWNAs), a class of organophosphorus compounds, is dependent on the choice of animal model used in preclinical studies. CWNAs bind to acetylcholinesterase and prevent the catalysis of acetylcholine, causing a plethora of peripheral and central physiologic manifestations, including seizure. Rodents are widely used to elucidate the effects of CWNA-induced seizure, albeit with a caveat: they express carboxyles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 50 publications
2
12
0
Order By: Relevance
“…Our laboratory and others previously reported on the beneficial effect of administering the NMDAR antagonist ketamine in combination with a benzodiazepine in reducing cholinergic‐induced seizure severity, epileptogenesis, functional impairment, and brain pathology in rodent models. 8 , 9 , 10 , 12 , 13 , 30 , 31 , 32 Previous studies also showed the importance of simultaneous administration of antiseizure medications, as opposed to sequential drug administration, in reducing cholinergic‐induced seizure severity. 33 The inclusion of a third antiseizure medication, valproate, in combination with ketamine and midazolam further reduces seizure severity, epileptogenesis, and neuronal loss following soman exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our laboratory and others previously reported on the beneficial effect of administering the NMDAR antagonist ketamine in combination with a benzodiazepine in reducing cholinergic‐induced seizure severity, epileptogenesis, functional impairment, and brain pathology in rodent models. 8 , 9 , 10 , 12 , 13 , 30 , 31 , 32 Previous studies also showed the importance of simultaneous administration of antiseizure medications, as opposed to sequential drug administration, in reducing cholinergic‐induced seizure severity. 33 The inclusion of a third antiseizure medication, valproate, in combination with ketamine and midazolam further reduces seizure severity, epileptogenesis, and neuronal loss following soman exposure.…”
Section: Discussionmentioning
confidence: 99%
“…In the rodent models of soman-induced SE, a treatment composed of midazolam and ketamine reduced seizure severity, ameliorated impairment in the Morris water maze, and reduced neuronal loss. [10][11][12][13] However, the protection afforded by the combination of ketamine and midazolam was incomplete, suggesting a need for an additional adjunct medical countermeasure. monotherapy (midazolam or phenobarbital) in reducing cholinergic-induced toxicity.…”
Section: Introductionmentioning
confidence: 99%
“… 22 This effect was also observed in soman exposed KIKO mice in which none of the mice treated with the dual therapy developed SRS, while all of the midazolam treated mice developed SRS. 88 In rats and Es1 −/− mice, dual therapy delayed the appearance of the first SRS but did not significantly reduce the number of SRS recorded for the first 14 days following SE exposure. However, midazolam–ketamine–valproate triple therapy not only increased the latency of the first SRS following soman exposure in rats but also significantly reduced the average number of SRS during the 2‐week period following treatment compared with midazolam monotherapy, showing the benefit of adding an additional ASM (valproate; Figure 11 ).…”
Section: Synergistic Effects Of Combination Therapy In Treating Epile...mentioning
confidence: 90%
“… 87 Similar to memantine's effects of increased survival, in severe soman‐induced seizure models in Es1 −/− and KIKO mice, ketamine in combination with midazolam increases survival and reduces neurodegeneration. 22 , 88 Other report that high‐dose memantine (56 mg/kg) in combination with midazolam administered 20 minutes after soman exposure resulted in high lethality, failed to terminate SE, but reduced delta power and cell death 89 ; high doses may induce seizure. 90 , 91 , 92 Although more research combining a low dose of memantine and other ASMs (benzodiazepine and/or nonbenzodiazepine drugs and anticholinergics) may be required to explore the therapeutic potential of memantine against OPNA exposure, studies with ketamine described in Sections 2 , 4 suggest that targeting NMDA receptors to reduce the effects of cholinergic‐induced SE is a beneficial strategy.…”
Section: Introductionmentioning
confidence: 99%
“…The transfer of genes that then generate transgenic animals that mimic or are immune to a disease. Transgenic animals that are immune to a disease can be used for testing of experimental medicines [12]- [14]. A variety of models of cancer are mainly studied in mice and rats.…”
Section: Generation Of Models For the Biomedical Studiesmentioning
confidence: 99%